WEBOMETRIC ANALYSIS OF WEBSITES OF CENTRAL UNIVERSITIES OF EASTERN INDIA: A STUDY (LIS TODAY, 2024)
The study presents the webometric analysis of the websites of 7 Central Universities of the  Eastern India region. The study aims to identify and evaluate the web presence, domain name,  Domain Authority, Page Authority, Google PageRank, Rich files, Language, and Social  Media presence of the selected websites under study. To accomplish the objectives of the  study, the Google search engine, some search engine optimization (SEO) tools, and manual  website visits have been used to analyse the websites under study. Major findings of the study  include that all universities' websites have the same Google PageRank value i.e. 4, the  website of Visva Bharti has the highest Domain Authority, Central University of Jharkhand's  website has the highest Page Authority, the website of Nalanda University is the single  website which uses only one language, i.e. English. All universities have their presence on  social media at different platforms. The study is unique and latest in the website analysis  category. Very few webometric studies have been conducted on the universities of the Eastern  region of India. This study is an effort to fill this gap. The present study concluded with some  suggestions that will be helpful for Policy-makers and Website developers to enhance their  websites and their visibility on the Web.
Keywords: Webometrics; Webometrics Web Analysis; Domain Analysis; Search Engine; Optimization; Moz; Rich Files; Academic Institutions